2007
DOI: 10.1002/cbf.1409
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of 2‐methoxyestradiol on cell morphology and Cdc2 Kinase activity in SNO oesophageal carcinoma cells

Abstract: The effects of 1 x 10 -6 M exogenous 2-methoxyestradiol (2 ME) were determined on cell morphology and cell division cycle (Cdc) 2 kinase activity in SNO oesophageal carcinoma cells. Mitotic indices revealed an increase in metaphase cells (11.2%) when compared to the 0.5% vehicle-treated cells after 18 h of exposure to 2 ME. Vehicletreated control cells did not show any hallmarks of apoptosis after 18 h of exposure to dimethyl sulphoxide. Only 0.5% of 2 ME-treated cells showed characteristics of apoptosis. Conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The GI 50 concentrations for the compounds are summarized in Table 1 . In in vitro studies conducted in our laboratory, 2‐ME showed an antiproliferative effect on HeLa, SNO, MCF‐7, and MCF‐12A cells in a concentration range of 1–2μ m (43–45). Accordingly, Edsall et al.…”
Section: Resultsmentioning
confidence: 99%
“…The GI 50 concentrations for the compounds are summarized in Table 1 . In in vitro studies conducted in our laboratory, 2‐ME showed an antiproliferative effect on HeLa, SNO, MCF‐7, and MCF‐12A cells in a concentration range of 1–2μ m (43–45). Accordingly, Edsall et al.…”
Section: Resultsmentioning
confidence: 99%
“…For example, 2ME 2 activates JNK kinases in prostate cancer cells [59], Ewing sarcoma cells [60,61] and nasopharyngeal carcinoma cells [62] to induce cell death by mitochondrial-dependent apoptotic pathways and/or autophagy. Furthermore, 2ME 2 activates a RNA-dependent protein kinase (PKR) [63] to induce autophagy in osteosarcoma cells and induces apoptosis in esophageal carcinoma cells by increasing cdc2 kinase activity [64].…”
Section: Modulation Of Protein Phosphorylation and Kinases Activitymentioning
confidence: 99%
“…Some potential mechanisms that might be involved in such an association are available. The presence of estrogen receptors in esophageal tissue has been identified, and in vitro studies indicate that estrogens might inhibit esophageal carcinogenesis [15][16][17]. Metabolites of lignans might lead to in vivo and vitro activation of estrogen receptor-mediated events [6].…”
Section: Introductionmentioning
confidence: 98%